Crowfunding: A Way to Financing Creative Business in Australia (JEJAK, 2013)
AbstractCrowdfunding, a new term in financial industries. It provides fund for a new start-up project. In Australia where it becomes the basis of this study, Pozible as a leading crowdfunding platform has already launched 6.929 projects. The fund of US$22.930.536 was used for financing the projects, and 56 percent of the projects were successful. This research has an objective; it is to measure the degree of significancy using linear regression model. The result shows that among the businesses that has already funded by crowdfunding system, ‘video game’ is one of the most favorite project. It is successful in getting pledges. However, food and drink did not get fund as much as the favorites project. It was based on the percentage of fund that has already got from crowdfunding. In short, crowdfunding can help creative business as a top rank start-up rather than manufacture business.Crowdfunding, istilah baru dalam industri keuangan. Crowdfunding adalah dana untuk proyek rintisan. Pozible sebagai platform crowdfunding terkemuka telah meluncurkan 6,929 proyek di Australia. Negara tersebut menjadi dasar dari penelitian ini. Dana sebesar $ 22.930.536 US digunakan untuk membiayai proyek-proyek dan 56 persen dari proyek tersebut sukses. Penelitian ini bertujuan untuk mengukur tingkat signifikansi dengan menggunakan model regresi linier. Hasilnya menunjukkan bahwa di antara bisnis yang sudah didanai oleh sistem crowdfunding, ‘video game’ adalah salah satu proyek yang paling favorit dan sukses dalam mendapatkan jaminan. Sedangkan makanan dan minuman tidak mendapatkan dana sebanyak proyek favorit. Hal ini didasarkan pada persentase dana yang telah diperoleh dari crowdfunding. Kesimpulannya adalah crowdfunding lebih bisa membantu bisnis kreatif sebagai a top rank start-up daripada bisnis manufaktur